Efektivitas Relaksasi Dzikir untuk Meningkatkan Motivasi Belajar Siswa : Literature Review - Fathimathuz Zahro; Abdul Muhid (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Background: In the learning process, students must have a stable motivation. Motivation is an inherent factor in everyone's learning activities. Human motivation is part of the need and becomes the most important part in encouraging someone to do something. However, it is often found that students have poor achievements not because of a lack of ability, but because they do not have the motivation to learn, so they do not try to develop their abilities to the fullest. Various efforts to increase student motivation in learning have been widely applied, but there is lack of attention to the internal factors of calm learning in students (inner calm).Purpose: This literature review tries to dig deeper into about the effectiveness of dhikr relaxation to increase students' learning motivation. Method: A writing method that uses literature review by collecting data from phenomena raised from various sources, both journals, books and references that are relevant to the issues and topics raised. Conclusion: The Dzikr relaxation method has very good effectiveness as a form of effort to increase student motivation to learn.